2017
DOI: 10.1016/j.schres.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aripiprazole lauroxil in schizophrenic patients presenting with severe psychotic symptoms during an acute exacerbation

Abstract: Aripiprazole lauroxil (AL), a new long-acting injectable antipsychotic, demonstrated safety and efficacy in treating acute exacerbation symptoms of schizophrenia in a 12-week placebo-controlled trial of two doses of AL (441 mg and 882 mg) administered every 4 weeks. We performed a post hoc analysis of this trial to evaluate the efficacy of AL in the subgroup of patients with severe psychotic symptoms, defined as those with baseline Positive and Negative Syndrome Scale (PANSS) Total score above the median score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Aripiprazole lauroxil (AL) is an intramuscular injectable extended-release prodrug of aripiprazole that is approved for the treatment of schizophrenia [ 5 , 6 ]. Pivotal clinical studies have demonstrated that AL 441 mg and 882 mg doses administered monthly (every 4 weeks [q4wk]) are efficacious [ 7 , 8 ] and population pharmacokinetic (PopPK) modeling provided the pharmacokinetic basis for the approval of the 662 mg dose q4wk and the 882 mg dose every 6 weeks (q6wk) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aripiprazole lauroxil (AL) is an intramuscular injectable extended-release prodrug of aripiprazole that is approved for the treatment of schizophrenia [ 5 , 6 ]. Pivotal clinical studies have demonstrated that AL 441 mg and 882 mg doses administered monthly (every 4 weeks [q4wk]) are efficacious [ 7 , 8 ] and population pharmacokinetic (PopPK) modeling provided the pharmacokinetic basis for the approval of the 662 mg dose q4wk and the 882 mg dose every 6 weeks (q6wk) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies reported that the placebo was intralipid (fat emulsion for human use). 19,21,22 The remaining studies did not describe the composition of the placebo. In all studies combined, the prevalence of any infection was 2.4% in the LAI antipsychotic group and 1.5% in the placebo group (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Mean study duration was 13 weeks, mean subject age was 39.5, mean % male was 71.5%, mean BMI was 27.3, and mean PANSS total score was 86.8. Three studies reported that the placebo was intralipid (fat emulsion for human use) 19,21,22 . The remaining studies did not describe the composition of the placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who recovered from their relapse moved to the “remission” health state. From all health states, patients could move to the absorbing health state “death.” Adverse events were not modeled because evidence regarding adverse events at different C min was unavailable and evidence also suggested that the safety profiles of AM and AL were similar [ 20 , 21 ]. The model had a cycle length of 2 weeks, which was the highest common denominator of the 4-, 6-, and 8-week regimens of the evaluated LAIs, was built in R version 4.0.2 [ 1 ], and made use of the RxODE package [ 2 ].…”
Section: Methodsmentioning
confidence: 99%